Adapting and Adopting: The Biblical Joseph as Received by Artapanus, Demetrius, and Philo the Poet in Third- and Second-Century BCE Egypt - Rabel, Magnus (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2025)
For many years, the fragmentary writings by Artapanus, Demetrius, and Philo the poet were insufficiently acknowledged for their profoundly illuminative content on Jewish thinking and acculturation. These fragments shed light on the perspectives of Egyptian-Jewish writers who sought not only to preserve their distinct Jewish roots but also to forge a connection with the intellectual and cultural milieu of Egypt. Central to this endeavor, yet hitherto somewhat insufficiently recognized in scholarly discussions, is the figure of the biblical Joseph, who conspicuously serves as an intermediary between these two objectives. As Jews deeply embedded within their adopted Egyptian culture, these authors endeavor in the extant fragments to provide a distinct perspective on the process of Jewish acculturation to foreign Egypt. Furthermore, they offer unparalleled insights into the reception of the figure of Joseph and his narrative in the third and second century BCE.